The Degree Centrality and Functional Connectivity in Patients With Temporal Lobe Epilepsy Presenting as Ictal Panic: A Resting State fMRI Study - Chang, Weiwei; Liu, Jinping; Nie, Liluo; Pang, Xiaomin; Lv, Zongxia; Zheng, Jinou (Frontiers in Neurology, 2022)
Objectives: Ictal panic (IP) can be observed occasionally in patients with temporal lobe epilepsy (TLE). Such descriptions can be found in previous study, but the mechanism is still not clear and often confused with panic attacks in panic disorder (PD) patients. We try to use imaging methods (resting-state functional magnetic resonance imaging, rs-fMRI) to study the mechanism of this psychiatric comorbidity in TLE patients. Methods: 40 right-onset TLE patients were observed, including 28 TLE without IP and 12 TLEIP patients along with 30 gender-age matched healthy controls were included. We collected clinical/physiological/neuropsychological and rs-fMRI data. Degree centrality (DC) and functional connectivity (FC) were calculated. For the DC and FC values, ANCOVA was used to find different areas and t-tests used to compare differences between TLEIP group, TLE without IP group and health controls（HCs）. The relationship between brain abnormalities and patient characteristics were explored by correlation analyses. Results：No significant differences in gender and age were found among the three groups, and no significant differences in education level, Montreal Cognitive Assessment (MOCA) , Hamilton Depressive Scale(HAMD), Hamilton Anxiety Scale (HAMA) and epilepsy duration(years) between the TLEIP group and TLE without IP group. In addition to fear, other symptoms were observed, including nausea, palpitations, rising epigastric sensation and dyspnea. There was no correlation between duration of IP and HAMA. Moreover, all IP durations were <2min. Compared to the HCs and TLE without IP group, the DC value of TLEIP group in the left middle temporal gyrus(LMTG) was significantly increased. Compared to the HCs, FC could be found between the LMTG and left inferior temporal gyrus(LITG) in TLEIP group. In addition, there was FC between LMTG and cerebellum in TLEIP group. And the difference in the magnitude of FC between the TLEIP vs HCs group was greater than the difference between TLE vs HCs group. Conclusions：This study describes brain abnormalities in TLEIP patients. These results will help to preliminarily understand the mechanism of ictal panic and abnormal functional connection in TLE patients, and further explore the neuroimaging mechanism of ictal panic in TLE patients.